Hemodynamic and Clinical Outcomes of Milrinone Compared to Dobutamine in Cardiogenic Shock: A-Systematic Review and Meta-Analysis - Bahagia, William; Santoso, Jimmy Oi (Jurnal Kardiologi Indonesia, 2025)
In “Hemodynamic and Clinical Outcomes of Milrinone Compared to Dobutamine in Cardiogenic Shock: A-Systematic Review and Meta-Analysis” (Indonesian Journal of Cardiology, 43(3), 108-15. https://doi.org/10.30701/ijc.1296), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1296. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1296